656.13 COORDINATION OF THE MOVEMENT OF TRANSPORT TYPES IN AREAS WITH HIGH PASSENGER FLOW: COORDINATION OF THE MOVEMENT OF TRANSPORT TYPES IN AREAS WITH HIGH PASSENGER FLOW - Yo'ldoshev, Davron; Mo'minov , To'lqin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Introduction. Today, many measures are being implemented to improve public transport infrastructure development. In particular, based on the decision of the President of the Republic of Uzbekistan №. PQ-111 dated February 2, 2022, comprehensive development of the public transport system of Tashkent city, providing quality and safe transport services to passengers, improvement of transport infrastructure, updating the traffic structure with modern buses with all amenities, in order to ensure road safety and create a comfortable environment for pedestrians, important tasks such as the organization of traffic links and coordination of traffic types have been defined at the intersections of surface public transport and metropolitan routes and in places with high traffic flow